FOXBASE APPLICATIONS TO THE FINANCIAL STATEMENTS AND DATA PROCESSING IN SEHAT PHARMACIES - Handi Handi; Drs. Eko Hadiyanto (Jurnal Sistem Informasi, 1996)
With the completion of the report KKP / PP, then the author can draw the conclusionthat the use of data processing applications and financial statements, then the processcan be done more quickly and accurately than the manual method, either in search ofdata and calculations.The research found that the flow of information in the pharmacy still not properlyorganized, is still going on disinformation in controlling the processing system.Where there is a responsible party should be looking for data - data that is requiredevery related party. Thus, this causes the ineffectiveness of time. So the author tries toadvance treatment system which requires that every party concerned is no t directlyreported on the details - details that occurred with the method of collecting data in astructured transaction via an appropriate route assignment.